PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA GURU YANG DIMODERASI OLEH IKLIM SEKOLAH DI MTS SEKECAMATAN WINONG KABUPATEN PATI - Suyati, 12.5202.0216; Suhari, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2016)
This study aimed to examine the effect of transformational leadership andmotivation to work on the performance of teachers in MTs Sekecamatan Winong Patiregency with school climate moderated. The specific objectives of this study was toexamine the effect of transformational leadership and motivation to work on teacherperformance that dmoderasi by climatic role. The usefulness of this study is to clarify andextend previous research on the effect of transformational leadership and motivation towork on teacher performance are moderated school climate.This study used a population of teachers in MTs Sekecamatan Winong Patiregency much as 121 teachers. Sampling techniques in this study is nonprobabilitysampling with purposive sampling method. Based on the results of the study can be summarized as follows: transformationalleadership influence on teacher performance, motivation does not affect the performanceof teachers, school climate affect the performance of the teacher, the influence oftransformational leadership on teacher performance is moderated by school climate, andthe effect on the performance of teachers' work motivation is not moderated by schoolclimate.Keywords: transformational leadership, motivation, school climate, teacher performance.